Between Old and New Media: Continuity, Transformation, and Research Challenges - Rianto, Puji; Desmalinda (Program Studi Ilmu Komunikasi, 2025)
Communication media have under-gone profound transformations since the emergence of the Internet in the 1990s, the rise of social media in the 2000s, and the launch of YouTube in 2005. By the 2010s, digital media had become firmly established as the dominant mode of communication and content consumption (Han, 2024). Several critical shifts can be identified as a result of the rise of new media. First, the role of professional media institutions as “gatekeepers” has significantly diminished. Users themselves have increasingly become the new “gatekeepers” of information (Rianto, 2016). Second, the long-standing idea of the active audience found its most radical expression in the digital media era (Rianto, 2016), characterized by the principles of interactivity and participation inherent in user-generated content (Lister et al., 2009). This participatory turn has blurred the boundaries between professional and user-generated content (Yu et al., 2024).